Diamonds in the Dark: Women in Romania - Carrescia, Olivia L. (Romania, 1999)
Soros Documentary Fund Women, survival, and transition in Romania in the late 1990s. From a traditional village bordering Ukraine, to the relatively sophisticated city of Bucharest, “Diamonds in the Dark” tells the stories of ten Romanian women. We hear and see how they lived under the old regime, and how they are confronting the new problems of the post-communist era. Archival footage and interviews relate the women's struggles for survival under Ceausescu. The chronic lack of heat and electricity, and the long lines for crumbs of food, were just the beginning of the burdens borne by women. Professionals, students, factory workers and farm-workers; all were obliged to take part in pro-Ceausescu demonstrations, take care of home and family, and produce more children for the regime. Abortion, the only form of birth control remotely available, was forbidden but common. These struggles were accompanied by a fear of surveillance, and a fear of expressing a viewpoint offensive to the regime. All of this within the historical context of traditional, patriarchal society that has shown few signs of becoming more egalitarian.